If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 16x = 10 + 15x Solving 4 + 16x = 10 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + 16x + -15x = 10 + 15x + -15x Combine like terms: 16x + -15x = 1x 4 + 1x = 10 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + 1x = 10 + 0 4 + 1x = 10 Add '-4' to each side of the equation. 4 + -4 + 1x = 10 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 10 + -4 1x = 10 + -4 Combine like terms: 10 + -4 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 8x+-7=-2x+5 | | 10+3x-x-4=x | | 13x+17+34=90 | | 8x+1+9x-7=180 | | Z-6=z-4 | | -2x-7=32 | | (4+8)n=36 | | (4+8)n=3 | | 10x-14=-2x-13 | | 772x= | | 10x-14=2x+13 | | 5y+39+4x+6=180 | | x(x+2)=1295 | | 9x-15=-5x-16 | | 9x-15=5x+16 | | n-8+3=5 | | 8x+2=4(6x-9) | | 26=2x-8+4x | | 8x+2=4-(6x-9) | | .6(X+100)+.8X=109 | | 104=2x+2(x+4) | | .2x+7.9=6.6 | | 60-5x=6 | | 6x+9y+5x+2y= | | -2x+3=4x-1 | | 10c^2+8c+12=-9 | | (-3)+17-6(-3)=2 | | (3x/3)=90 | | 5(8x-5)+7=32 | | 4590=40t^4+1560t^2 | | 10c+8c+12=-9 | | .17y+.04(y+8000)=2000 |